Diet of buffy tufted-eared marmosets (Callithrix aurita) in a forest fragment in southeastern Brazil - Martins, M. M.; Setz, EZF (Kluwer Academic/plenum Publ, 2000)
The feeding ecology of the Atlantic forest marmosets (Callithrix spp.) in southeastern Brazil is poorly known, and few studies have focused on buffy tufted-eared marmosets, Callithrix aurita. We determined the food items and investigated the seasonal variation in the diet of a group of four Callithrix aurita in a 17-ha semideciduous forest fragment in southern Minas Gerais State, Brazil. We recorded daily feeding activities between October 1994 and September 1995 using scan sampling at 5-min intervals. The marmosets devoted feeding rime to gums (50.5%), fruits (11%), and animal prey (38.5%) in a fetal of 499 records. Plant resources comprised 27 species from 16 families. They used Acacia paniculata (Mimosoideae, Leguminosae), the main gum source (82%), year-round Maclura tinctoria (Moraceae) was the fruit species that they consumed most (22%). The marmosets preyed on caterpillars (33%), katydids (5%), and homopterans (4%). Feeding on fruits varied seasonally and was inversely related to gum feeding. Consumption of animal prey remained constant over the year. The wide and year-round dependence on gum suggests that Acacia may play a critical role in marmoset persistence in forest fragments.
Keywords: Callithrix aurita; diet; forest fragment; seasonality; southeastern Brazil